Hubungan Kompetensi Perawat Tentang Transcultural Nursing Dengan Pengalaman Pelaksanaan Komunikasi Terapeutik di Ruang Rawat Inap Interna RSU GMIM Pancaran Kasih Manado - Devina Triana Ponengoh; Irma M. Yahya; Silvia Dewi Mayasari Riu (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Transcultural nursing theory (transcultural nursing), this theory is seen as knowledge about individuals, families, groups, communities, and institutions in diverse health care systems. The aim of this research is to determine the relationship between nurse competency regarding transcultural nursing and experience in implementing therapeutic communication in the internal inpatient room at RSU GMIM Pancaran Kasih Manado. This research design uses descriptive analysis with a cross sectional approach. The sample in this research was carried out using total sampling, namely the sampling technique is the same as the population size. So the total sample in the study was 36 nurses. Data collection was carried out by direct interviews with subjekts and distributing questionnaires. Furthermore, the data that had been collected using computer assistance with IBM SPSS Version 23 was analyzed using the chi-square test with a significance level (α) <0.05. The results of the research using the Chi-Square Test show a p value of 0.003, which is smaller than α ≤0.05, meaning Ha is accepted and Hο is rejected. The conclusion in this research is that there is a relationship between nurse competency regarding transcultural nursing and experience in implementing therapeutic communication in the internal inpatient room at RSU GMIM Pancaran Kasih Manado. It is hoped that the results of this research will allow nurses to respond to and carry out nursing care from cultural diversity by using therapeutic communication that can be adapted to the patient's condition.